1984
DOI: 10.1210/endo-115-6-2260
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Hypophysis in Regulation of Pancreatic and Gastric Somatostatin

Abstract: Since hypophysectomy and GH deficiency are associated with decreases in hypothalamic content and release of SRIF, it was of interest to determine whether these hormonal alterations also affect peripheral tissue levels of SRIF. Hypophysectomized (hypox) rats were studied at various times after surgery and compared with age-matched controls. Pancreatic, gastric, and hypothalamic SRIF levels were measured by RIA and expressed as nanograms per mg protein or nanograms per organ. Decreased levels of hypothalamic SRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Thus, GH deficiency after hypophysectomy results in a decrease in the hypothalamic somatostatin content in vivo and its release in vitro (Berelowitz et al 1981). In contrast, pancreatic somatostatin has been reported to be increased in rats 4-6 weeks after hypophysectomy (Recant et al 1984). The latter result agrees with the results of the present study with respect to the pancreatic somatostatin peptide content.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, GH deficiency after hypophysectomy results in a decrease in the hypothalamic somatostatin content in vivo and its release in vitro (Berelowitz et al 1981). In contrast, pancreatic somatostatin has been reported to be increased in rats 4-6 weeks after hypophysectomy (Recant et al 1984). The latter result agrees with the results of the present study with respect to the pancreatic somatostatin peptide content.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, islets isolated and cultured 4 weeks after hypophysectomy contained less insulin per microgram of protein than islets from normal rats (Martin and Gagliardino 1967). Pancreatic somatostatin per gram of tissue was found to be unchanged (Berelowitz et al 1981) whereas Recant et al (1984) found elevated somatostatin whether expressed per milligram of protein or per whole pancreas of hypox rats. To our knowledge, no data are available regarding pancreatic glucagon content in hypox rats.…”
Section: Introductionmentioning
confidence: 85%